The stress kit: a new method based on competitive reverse transcriptase–polymerase chain reaction to quantify the expression of human αB-crystallin, Hsp27, and Hsp60 - Bajramović, Jeffrey J.; Geutskens, Sacha B.; Bsibsi, Malika; Boot, Marit; Hassankhan, Ryan; Verhulst, Karien C.; van Noort, Johannes M. (Cell stress & chaperones, 2000)
We describe a reverse transcriptase–polymerase chain reaction method for the semiquantitative detection of mRNAs encoding the human heat shock proteins αB-crystallin, Hsp27, and Hsp60. The method involves the coamplification of cellular mRNA-derived cDNA with a dilution series of a competitor fragment (internal standard), using 1 primer pair common to both templates. Internal standards were based on cellular-derived cDNA engineered to be slightly smaller to differentiate between the target and the standard on electrophoretic separation. Initial cDNA quantitations can be corrected for possible variations during cDNA synthesis by standardizing to the levels of β-actin–encoding cDNA. We show that the coamplified templates accumulate in a parallel manner with the cellular-derived cDNA throughout both the exponential and the nonexponential phase of amplification. Furthermore, we illustrate the utility of this technique by quantifying increased expression of αB-crystallin, Hsp27, and Hsp60 mRNA in astroglioma cells on heat shock.